Ответ:
↓↓↓↓↓↓↓↓↓↓↓↓
Объяснение:
x=-13 →
x=-5 →
x=-0.2 →
x=0 →
x=1\17 → = -1.72
x=1 →
x=5 2\3 → =4
x=7 →
..............,........
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
↓↓↓↓↓↓↓↓↓↓↓↓
Объяснение:
x=-13 →![\frac{-13+5}{-13-3}=\frac{-8}{-16} =\frac{1}{2} \frac{-13+5}{-13-3}=\frac{-8}{-16} =\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-13%2B5%7D%7B-13-3%7D%3D%5Cfrac%7B-8%7D%7B-16%7D%20%3D%5Cfrac%7B1%7D%7B2%7D)
x=-5 →![\frac{-5+5}{-5-3}=\frac{0}{-8} =0 \frac{-5+5}{-5-3}=\frac{0}{-8} =0](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B5%7D%7B-5-3%7D%3D%5Cfrac%7B0%7D%7B-8%7D%20%3D0)
x=-0.2 →![\frac{-0.2+5}{-0.2-3}=\frac{4.8}{-3.2} = -1.5 \frac{-0.2+5}{-0.2-3}=\frac{4.8}{-3.2} = -1.5](https://tex.z-dn.net/?f=%5Cfrac%7B-0.2%2B5%7D%7B-0.2-3%7D%3D%5Cfrac%7B4.8%7D%7B-3.2%7D%20%3D%20-1.5)
x=0 →![\frac{0+5}{0-3}=\frac{5}{-3} =-\frac{5}{3} \frac{0+5}{0-3}=\frac{5}{-3} =-\frac{5}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B0%2B5%7D%7B0-3%7D%3D%5Cfrac%7B5%7D%7B-3%7D%20%3D-%5Cfrac%7B5%7D%7B3%7D)
x=1\17 →
= -1.72
x=1 →![\frac{1+5}{1-3}=\frac{6}{-2} =-3 \frac{1+5}{1-3}=\frac{6}{-2} =-3](https://tex.z-dn.net/?f=%5Cfrac%7B1%2B5%7D%7B1-3%7D%3D%5Cfrac%7B6%7D%7B-2%7D%20%3D-3)
x=5 2\3 →
=4
x=7 →![\frac{7+5}{7-3}=\frac{12}{4} =3 \frac{7+5}{7-3}=\frac{12}{4} =3](https://tex.z-dn.net/?f=%5Cfrac%7B7%2B5%7D%7B7-3%7D%3D%5Cfrac%7B12%7D%7B4%7D%20%3D3)
Verified answer
Ответ:
Объяснение:
..............,........